Plekhg5-regulated autophagy of synaptic vesicles reveals a pathogenic mechanism in motoneuron disease. Issue 1 (December 2017) - Lüningschrör, Patrick; Binotti, Beyenech; Dombert, Benjamin; Heimann, Peter; Perez-Lara, Angel; Slotta, Carsten; Thau-Habermann, Nadine; R. von Collenberg, Cora; Karl, Franziska; Damme, Markus; Horowitz, Arie; Maystadt, Isabelle; et al.
Abstract Autophagy-mediated degradation of synaptic components maintains synaptic homeostasis but also constitutes a mechanism of neurodegeneration. It is unclear how autophagy of synaptic vesicles and components of presynaptic active zones is regulated. Here, we show that Pleckstrin homology containing family member 5 (Plekhg5) modulates autophagy of synaptic vesicles in axon terminals of motoneurons via its function as a guanine exchange factor for Rab26, a small GTPase that specifically directs synaptic vesicles to preautophagosomal structures.Plekhg5 gene inactivation in mice results in a late-onset motoneuron disease, characterized by degeneration of axon terminals. Plekhg5-depleted cultured motoneurons show defective axon growth and impaired autophagy of synaptic vesicles, which can be rescued by constitutively active Rab26. These findings define a mechanism for regulating autophagy in neurons that specifically targets synaptic vesicles. Disruption of this mechanism may contribute to the pathophysiology of several forms of motoneuron disease. Accumulating evidence suggests that disruption of autophagy is associated with neurodegeneration. Here the authors show that Plekhg5 acts as a GEF for Rab26, a small GTPase that promotes the autophagy of synaptic vesicles in neurons; mice lacking Plekgh5 develop late-onset motoneuron degeneration.